Deconstruction of Cultural Hegemony in Nepali Society: A Study of Sumnima - Kandel, Bhanu Bhakta Sharma (The Outlook: Journal of English Studies, 2022)
BP Koirala’s novel Sumnima has raised an issue that how cultural hegemony has been being practised in Nepali society on the basis of racial, political and cultural superiority of a certain group of people over the others. The main objective of studying the novel in this article is to find how the novelist has deconstructed the cultural superiority of the privileged group and has made the family lineage of the dominant race has dissolved into the lineage of the marginalized group. The critical insights by deconstruction and new-historicism have been used to analyze the primary text. The study examines and analyzes how the relations without understanding cannot prosper even within the same ethnic group but love and understanding make the life beautiful no matter which tribe or ethnicity the people belong to. The researcher has found, having studied the text that nature is superior to nurture, a culture does not become superior by having practised by a certain group of people nor being educated adds to the wisdom in the people because wisdom is rather natural an attribute.